Morphological modifications of electrodeposited calcium phosphate coatings under amino acids effect - Drevet, R.; Lemelle, A.; Untereiner, V.; Manfait, M.; Sockalingum, G.D.; Benhayoune, H. (Applied surface science, 2013)
► Calcium phosphate coatings are electrodeposited on titanium alloy substrates. ► Amino acids are added to the electrolyte to direct the calcium phosphate growth. ► Amino acids modify the coatings morphology without structural or chemical change. ► These morphological modifications improve the corrosion behaviour of the material. Calcium phosphate coatings are synthesized on titanium alloy (Ti6Al4V) substrates by pulsed electrodeposition. This work aims to observe the morphological modifications of the coating when an amino acid is added to the electrolytic solution used in the process. The effects of two amino acids (glutamic acid and aspartic acid) are studied at a low and a high concentration. The coating morphology is observed at a nanometer scale by field emission gun-scanning electron microscopy (FEG-SEM). The structural characterization of the coating is performed by Fourier transformed infrared spectroscopy (FT-IR), Raman spectroscopy and X-ray diffraction (XRD). Moreover, corrosion measurements of the prosthetic surfaces are carried out by potentiodynamic polarization experiments in a physiological solution named Dulbecco's modified eagle medium (DMEM). The results show that the addition of an amino acid to the electrolytic solution leads to the decrease of the size of the crystallites which compose the prosthetic calcium phosphate coating that becomes denser and less porous than the coatings obtained without amino acid. Consequently, the corrosion behavior of the prosthetic material immersed in DMEM is improved.